Kebar Grass Extract (Biophitum Petersianum) Increases Diameter Of The Seminiferous Tubules Of Diabetic Mice - Faraida Arvilla (Saintika Medika, 2021)
Diabetes is a metabolic disease that can affect the male reproductive system. The condition of hyperglycemia will increase the production of ROS, causing oxidative stress. Oxidative stress causes microangiopathy, triggers cell apoptosis, interferes with spermatogenesis, thereby affecting the diameter of the seminiferous tubules. Kebar grass contains of flavonoid and vitamin E which can be used to reduce ROS reactions and inhibit oxidative stress. This research was to prove that kebar grass extract can increase diameter of the seminiferous tubules of diabetic mice. Total of 30 samples were divided into 5 groups: negative control group (K-) was given CMC-Na, positive control group (K+) was given metformin 2mg/kg, groups P1, P2 and P3 received 2mg/kg metformin and kebar grass extract with different dosages (67.5mg/kg, 135mg/kg and 270mg/kg). The treatment lasted for 35 days. On the 36th day the mice were sacrificed and the testes were taken, then histological observations were made with HE staining to measure the diameter of tubules. The result showed that there was a significant difference in the diameter of seminiferous tubules with p value=0,000. Kebar grass extract can increase the diameter of seminiferous tubules of diabetic mice.